Economic growth and distribution : on the nature and causes of the wealth of nations - Salvadori, Neri. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
The book isolates and compares the logical structures and methodological underpinnings underlying the relationship between economic growth and distribution. It carries out in-depth analysis of a wide range of of issues connected with growth theory considered from different theoretical perspectives. Its uniqueness is derived from the original contributions by a number of scholars of different persuasions.
Includes bibliographical references and index.
opc 09/01/17
Loans
Keywords: Economic development; Endogenous growth (Economics); Distribution (Economic theory)